2016
DOI: 10.1021/acs.macromol.6b01414
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Energy Levels and Blend Morphology for All-Polymer Solar Cells via Fluorination of a Naphthalene Diimide-Based Copolymer Acceptor

Abstract: We investigate the photovoltaic properties and charge dynamics of all polymer solar cells (all-PSCs) based on poly­[(N,N′-bis­(2-octyl­dodecyl)­naphthalene-1,4,5,8-bis­(dicarboximide)-2,6-diyl)-alt-5,5′-(2,2′-bithiophene)] (P­(NDI2OD-T2)) and its fluorinated analogue, poly­[(N,N′-bis­(2-octyl­dodecyl)­naphthalene-1,4,5,8-bis­(dicarboximide)-2,6-diyl)-alt-5,5′-(3,3′-difluoro-2,2′-bithiophene)] (P­(NDI2OD-T2F)), as the acceptor polymer and poly­[4,8-bis­(5-(2-ethyl­hexyl)­thiophen-2-yl)­benzo­[1,2-b:4,5-b′]­dith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 77 publications
1
73
0
1
Order By: Relevance
“…As the electron‐withdrawing property of the Pt complex is weaker than the NDI moiety, therefore, the HOMO and LUMO rises with the introduction of Pt complex ratio in the terpolymers compared in PNDIT2 copolymers. And the HOMO and LUMO values for PNDIT2 measured in this work was in good agreement with literature reported values of −5.7 – −6.0 and −3.5 – −3.8 eV …”
Section: Resultssupporting
confidence: 92%
“…As the electron‐withdrawing property of the Pt complex is weaker than the NDI moiety, therefore, the HOMO and LUMO rises with the introduction of Pt complex ratio in the terpolymers compared in PNDIT2 copolymers. And the HOMO and LUMO values for PNDIT2 measured in this work was in good agreement with literature reported values of −5.7 – −6.0 and −3.5 – −3.8 eV …”
Section: Resultssupporting
confidence: 92%
“…This same fluorinated polymer 31 a was also reported by Woo and co‐workers. When mixed with D11 , a PCE of 6.09 % was attained with a V oc of 1.00 V, J sc of 11.68 mA cm −2 , and FF of 52 % . F‐containing NDI‐based polymer 32 was synthesized by Ong et al.…”
Section: Ndi‐based Polymer Semiconductorsmentioning
confidence: 99%
“…When mixed with D11,aP CE of 6.09 %w as attainedw ith a V oc of 1.00 V, J sc of 11.68 mA cm À2 ,a nd FF of 52 %. [44] F-containing NDI-based polymer 32 was synthesized by Ong et al The resulting polymer showed ah igher absorptivity and increased intensityo fp-p stacking. The all-PSCs based on D1 as the donor polymer showed aP CE of 5.20 %.…”
Section: Introductionmentioning
confidence: 99%
“…The high-performance all-PSCs with PCEs over 7% only afford moderate V oc around 0.8 V, [18,22,24,26,28] whereas a few all-PSCs can emerge high V oc around 1.0 V, but the PCEs never surpass 7%. [20,[29][30][31][32] In contrast, a PC 71 BM-based PSC with a high V oc close to 1 V and a high PCE of 8.9% has been realized. [33] A nonfullerene PSC based on a polymer/small molecule blend also attained a high V oc of 1.12 V with a high PCE approaching 10%.…”
mentioning
confidence: 94%
“…[15][16][17][18][19][20][21] However, the PCEs of the record all-PSCs are still behind those of the state-of-the-art PC 71 BM-based PSCs. [22][23][24][25][26] Among the high-performance all-PSCs to date, a relatively high short-circuit current density (J sc ) of 18.6 mA cm −2 , [27] or a high fill factor (FF) over 0.7 are achieved individually, [24,26,28] approaching to those of the record-efficiency PC 71 BM-based PSCs.…”
mentioning
confidence: 99%